PEKERJA IMIGRAN TANPA DOKUMEN MELALUI JALUR LAUT DI PULAU KECIL: MASALAH HUKUM DAN SOLUSI KEBIJAKAN - nurainun, nurainun; Sepriani, Elsa; Sukino (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2025)
The sea is used as a crossing route to get to neighboring countries, either as an immigrant worker with complete documents or without documents. The purpose of this law is to regulate every field of marine resource utilization for the fulfillment of human life needs, especially as a means of transportation. This type of research uses normative legal research, data analysis in this research is carried out qualitatively. The data used are primary data and secondary data with the method of drawing conclusions in this study carried out deductively. The conclusion of this paper is that there are still many undocumented immigrant workers by sea in Pulau Kecil triggered by economic factors, low levels of education, lack of knowledge about the law and it has become a habit for the community when they do not have a job and have graduated from school to work in Malaysia. Undocumented immigrant workers are the biggest trigger for the emergence of human trafficking crimes, this shows the importance of education to the community and the immigration office should be able to provide an understanding of the dangers that occur